Solid CaCO3 Formation in Glioblastoma Multiforme and its Treatment with Ultra-Nanoparticulated NPt-Bionanocatalysts - López-Goerne, Tessy; Arellano, Alfonso; Padilla-Godínez, Francisco J.; Magaña, Carlos; González-Bondani, Antonela; Valiente, Rafael (Current Cancer Drug Targets, 2025)
BackgroundGlioblastoma multiforme (GBM), the most prevalent form of central nervous system (CNS) cancer, stands as a highly aggressive glioma deemed virtually incurable according to the World Health Organization (WHO) standards, with survival rates typically falling between 6 to 18 months. Despite concerted efforts, advancements in survival rates have been elusive. Recent cutting-edge research has unveiled bionanocatalysts with 1% Pt, demonstrating unparalleled selectivity in cleaving C-C, C-N, and C-O bonds within DNA in malignant cells. The application of these nanoparticles has yielded promising outcomes.ObjectiveThe objective of this study is to employ bionanocatalysts for the treatment of Glioblastoma Multiforme (GBM) in a patient, followed by the evaluation of obtained tissues through electronic microscopy.MethodsBionanocatalysts were synthesized using established protocols. These catalysts were then surgically implanted into the GBM tissue through stereotaxic procedures. Subsequently, tissue samples were extracted from the patient and meticulously examined using Scanning Electron Microscopy (SEM).Results and DiscussionDetailed examination of biopsies via SEM unveiled a complex network of small capillaries branching from a central vessel, accompanied by a significant presence of solid carbonate formations. Remarkably, the patient subjected to this innovative approach exhibited a three-year extension in survival, highlighting the potential efficacy of bionanocatalysts in combating GBM and its metastases.ConclusionBionanocatalysts demonstrate promise as a viable treatment option for severe cases of GBM. Additionally, the identification of solid calcium carbonate formations may serve as a diagnostic marker not only for GBM but also for other CNS pathologies.
Keywords: NPt